Association of Time to Antibiotic Administration with Hospital Outcomes in Children with Cancer having Febrile Neutropenia: A Prospective Observational Study (Bangladesh Renal Journal, 2026)
Background: Febrile neutropenia (FN) is a leading cause of morbidity and mortality in children with cancer. Prompt empirical antibiotic therapy is the cornerstone of management of FN and time to antibiotic (TTA) administration has been proposed as a quality of care measure.Objective: To evaluate the association between TTA and hospital outcomes in children with cancer having FN.Methods: This prospective observational study enrolled 40 children with cancer having FN (absolute neutrophil count